Exploring multi-target inhibitors using in silico approach targeting cell cycle dysregulator–CDK proteins. Issue 19 (15th November 2022) - Ahmed, Basharat; Khan, Sara; Nouroz, Faisal; Farooq, Umar; Khalid, Saba
Abstract: Cyclin-dependent kinases (CDKs) belong to a family of multifunctional enzymes that control cell cycle modifications, transcription, and cell proliferation. Their dysfunctions result in different diseases like cancer making them an important drug target in oncology and beyond. The present study aims at identifying the selective inhibitors for ATP binding site in CDK proteins (CDK1, CDK2, CDK4, and CDK5) following a multi-target drug designing approach. Significant challenges lie in identifying the selective inhibitor for the ATP binding site as this region is highly conserved in all protein kinases. Molecular docking coupled with molecular dynamics simulation and free energy of binding calculations (MMPBSA/MMGBSA) were used to identify the potent competitive ATP binding site inhibitors. All the four proteins were docked against the library of drug-like compounds and the outcomes of the docking study were further analyzed by Molecular dynamics (total of 6 μ s) and MMPB/GBSA techniques. Five different inhibitors for structurally distant protein kinases, i.e. CDK1, CDK2, CDK4, and CDK5 are identified with the binding energy (Δ G bind -PB) in the range −18.24 to −28.43Kcal/mol. Mechanistic complexities associated with the binding of the inhibitor are unraveled by carefully analyzing the MD trajectories. It is observed that certain residues (Lys33, Asp127, Asp145, Tyr15, Gly16, Asn144) and regions are critical for the retention of inhibitors in active pocket, and significant conformational changes take place in the active site region as well as its neighbor following the entry of the ligand inside active pocket as inferred by RMSD and RMSF. It is observed that LIG3 and LIG4 are the best possible inhibitors as reflected from their high binding energy, interaction pattern, and their retention inside the active pocket. This study will facilitate the process of multi-target drug designing against CDK proteins and can be used in the development of potential therapeutics against different diseases. Graphical Abstract: UF0001 Communicated by Ramaswamy H. Sarma